2018
DOI: 10.4236/tel.2018.814189
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Profitability of Banks in India

Abstract: The paper examines the factors influencing the profitability of Indian commercial banks considering increased globalization, intensified competition, and enhanced concentration. The sample is a balanced panel dataset of 89 banks operating in India for the period 2005 to 2015. We consider the return on assets (ROA) and the return on equity (ROE) as proxy for measurement of banks' profitability. The results indicate that profitability of banks in India is affected by both internal and external factors. Strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…For India, DAR, DTAR, and DER are found positive and significant but EAR, GDPGR, and IR are found to be negative and significant with ROA ( Tables 10 , 11 ). Thus, the analysis proves that there is a difference between Bangladesh and India (Tan, 2016 ; Brahmaiah, 2018 ) on the basis of banks' specific and macroeconomic factors. So, null hypothesis (H3) is hereby rejected.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For India, DAR, DTAR, and DER are found positive and significant but EAR, GDPGR, and IR are found to be negative and significant with ROA ( Tables 10 , 11 ). Thus, the analysis proves that there is a difference between Bangladesh and India (Tan, 2016 ; Brahmaiah, 2018 ) on the basis of banks' specific and macroeconomic factors. So, null hypothesis (H3) is hereby rejected.…”
Section: Discussionmentioning
confidence: 86%
“…Hasanov et al ( 2009 ) and Syathiri et al ( 2020 ) discovered that the size of a bank, the number of loans it makes, and the amount of money it lends out are all factors. Bank profitability is impacted by the adequacy of financial assets, the deposit-to-GDP level, and the operating efficiency, according to Brahmaiah ( 2018 ). Mohanty and Krishnankutty ( 2018 ) looked into the profitability of Indian banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Profit is considered to be the ultimate destination of the commercial banks’ performance (Ongore & Kusa, 2013; Robin et al, 2018), and over the last several years, bank’s profitability has been comprehensively studied in various countries across the globe (Almaqtari et al, 2019). Almost all studies lay stress on the internal or bank-related factors and external or macroeconomic factors influencing commercial banks’ performance (Abdullah et al, 2014; Al-Homaidi et al, 2018; Almaqtari et al, 2019; Anbar & Alper, 2011; Antoun et al, 2018; Athanasoglou et al, 2008; Brahmaiah & Ranajee, 2018; Caporale et al, 2017; Curak et al, 2012; Demirgüç-Kunt & Huizinga, 1999; Dietrich & Wanzenried, 2014; Ebenezer et al, 2017; Flamini et al, 2009; Gul et al, 2011; Jara-Bertin et al, 2014; Kamarudin et al, 2016; Le & Ngo, 2020; Luft & Omarkhil, 2018; Molyneux & Thornton, 1992; Masood et al, 2015; Muhammad, 2015; Ongore & Kusa, 2013; Pasiouras & Kosmidou, 2007; Petria et al, 2015; Rashid & Jabeen, 2016; Saeed, 2014; Saona, 2016; Subbarayan & Jothikumar, 2017; Yahya et al, 2017; Yao et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…4. Brahmaiah, B. and Ranajee (2018) 4 , revealed that the GDP growth and inflation has a bad effect in association with the return on assets (ROA) and inflation has good effect on the return on equity (ROE) which taken 89 banks functioning in India for a period of 10 years from 2002 to 2015. 5.…”
Section: Introductionmentioning
confidence: 99%